2018
DOI: 10.1002/slct.201802002
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antileishmanial Activity of a Triazole‐Based Hybrid Peptide against Leishmania major

Abstract: The dipeptides 1–4 with a triazole containing synthetic amino acid and Leu/ Phe/ Val/ Gly have been designed and synthesized as a potent antileishmanial agent. The 1‐(2‐Amino‐phenyl)‐1H‐[1, 2,3] triazole‐4‐carboxylic acid was synthesized using click chemistry approach. From X‐ray crystallography, the peptide 1 containing a Leu residue at C‐terminus adopts kink like structure but there is no intramolecular hydrogen bond. So, the hydrogen bonding sites are free and allowed for intermolecular interaction with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Several authors have reported the use of different 1,2,3-triazole derivatives as potential antileishmanial agents [27][28][29]. According to our results on activity against promastigote forms, compounds 2, 4, 5, and 6 showed significant results.…”
Section: Discussionsupporting
confidence: 56%
“…Several authors have reported the use of different 1,2,3-triazole derivatives as potential antileishmanial agents [27][28][29]. According to our results on activity against promastigote forms, compounds 2, 4, 5, and 6 showed significant results.…”
Section: Discussionsupporting
confidence: 56%
“…11) has promising anti-leishmanial activity. 123 The IC 50 value calculated based on normal growth inhibition and IC 50 value of 93 on Leishmania major promastigotes was 11 μg/mL. The most relevant factors were the cytotoxicity, lipophilicity and antiparasitic activity of the lead compounds a substantial points for the design of a new anti-leishmanial agents.…”
Section: Anti-leishmanial Activitymentioning
confidence: 99%
“…1,2,3-Triazole-containing compounds have been widely investigated because they are considered privileged scaffolds in different areas of medicinal chemistry, 36 38 including several examples in the antileishmanial field. 39 Interest in this molecular architecture has also been fueled by its expedient synthesis through “click chemistry”. 40 In this scenario, we decided to apply the bioisosteric replacement of imidazole by 1,2,3-triazole in our recently described imidazole-phenyl-thiazoles.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3-Triazole-containing compounds have been widely investigated because they are considered privileged scaffolds in different areas of medicinal chemistry, including several examples in the antileishmanial field . Interest in this molecular architecture has also been fueled by its expedient synthesis through “click chemistry” .…”
Section: Introductionmentioning
confidence: 99%